Granulomatosis with polyangiitis - Yu Zhu; Jiao Zhu; Rui Luo; Deping Wang; Cuiying Zhou (IDCases, 2024)
A 30-year-old man presented to otolaryngology department complaining of nasal congestion and runny nose for six months, with repeated fever, and shortness of breath.The weight loss in the past 20 days was about 5 kg. At first, he was diagnosed with respiratory infection and was treated with antibiotics, but it didn't work. Nasopharynx CT scan showed soft tissue thickening without bone destruction, with obvious inhomogeneous enhancement. Chest CT scan revealed multiple patchy clouding nodules and ground-glass opacity with poorly-defined border. Urine test showed urine microalbumin ≥ 150 mg per liter (reference range, 0–20), white-cell count of 11.0 cells per microliter (reference range, 0–5). Histology of nasopharynx biopsy showed small-medium-vessel necrotizing vasulitis.Although nasopharyngeal histopathology didn’t reveal peri- and extravascular granulomatosis and antineutrophilic cytoplasmic antibodies (ANCA) was negtive, he had ENT signs, lung nodules, and kidney involvement and condition developed fast and biopsy showed small- and- medium-vessel vasculitis. Therefore, the patient met the classification criteria for GPA and his symptoms were disappeared 1 week after starting GPA treatment, the chest CT showed ground-glass opacity decreased and CRP、ESR became normal. He was treated with rituximab combined with glucocorticoids for 4 weeks, after which he was discharged.